Ghostly Presences OUT THERE: Transgender Girls and Their Families in the Time of COVID. Issue 3 (1st December 2020) - Campbell Galman, Sally
Abstract : Meet Lily: Hi! I'm Lily. I'm 12 years old and I'm going into junior high school next year. I have curly black hair like my dad and green eyes like my mom. It's been 170 days since school and life and shops and stuff all shut down and my little sister Chloe and I really REALLY want COVID to be over. We play dolls and read and go for walks but I also spend a lot of time online texting and stuff with my friends.